Exploring the Research Trends-Related Imbalances in Doctoral Level Research on Distance Education in Pakistan: Muhammad Musaud Asdaque* Syed Asad Abbas Rizvi** (PJDOL, 2023)
The areas of research and methodological dimensions in the distance education are expanding rapidly due to technological advances (Wong et al., 2016). This research intends to investigate the imbalances in domains of research topics and methodological dimensions in the doctoral level dissertations at Allama Iqbal Open University (AIOU) between 2001- 2014. The 37 PhD dissertations accessed from the Higher Education Commission (HEC)’s research repository were selected as the sample of this study, which were reviewed to record the research topics, research types/models, data collection tools and data analysis instruments andcategories of the participants. Keywords: Ph.D dissertations, distance education, Allama Iqbal Open University, Higher Education Commission